A new species of Anthurium sect. Cordato-punctatum (Araceae) from Veracruz, Mexico - Díaz Jiménez, Pedro; Carrera-Sánchez, Edith; Croat, Thomas B.; Pérez-Farrera, Miguel Ángel; Gómez-Marín, Francisco J.; Hentrich, Heiko; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2023)
Anthurium knopflmacherianum, a new species of Anthurium sect. Cordato-punctatum, is registered for the region of Los Tuxtlas,Veracruz, Mexico. This new species is morphologically similar to A. verapazense, but that species differs in having shorter geniculum, longer anterior lobe, inflorescence with a longer peduncle and longer spadix, violet-purple at anthesis.